Elisa evaluation of the levels of antibodies against Infectious Bronchitis Virus in laying hens using egg yolk as substrate - Rauber,RH (2004)
The present work was carried out to compare Infectious Bronchitis Virus (IBV) antibody titers in serum and egg yolk samples from laying hens. Sixty paired blood and egg samples were collected from laying hens of two farms. Serum samples were frozen, while egg yolk samples were diluted (1:500) before freezing. Serum and yolk samples were tested for the presence of IBV antibodies by indirect ELISA (commercial kit) and titers were compared by a correlation test (alpha=0.05). There was a high correlation (r=0.62) between the two kinds of samples, which means that titers of IBV antibodies in the egg yolk and in serum samples are quite the same. Considering that blood collection causes deep stress that leads to economic losses, and since eggs are collected daily on the farm, results reported here are of importance to poultry production.